A Study of Appropriate Caring the Elderly: a Case Study of the Elderly Population in Rim Klong Lat Phrao Community, Chandrakasem Subdistrict, Chatuchak District, Bangkok - ขอพลอยกลาง ธีระศักดิ์; ลาดคุ้ม กอบทอง (Journal of Health Science of Thailand, 2024)
The purposes of this research were to study the suitable patterns of public health care for elderly and to develop the suitable patterns for elderly public health care. The samples were 30 elderly in Lim Klong Lad Proa community, Bangkok, selected by purposive sampling, and 15 public health care volunteers. The instruments used in this research were questionnaires and interviewing. The statistics used to analyze the data were frequency, percentage, mean, standard deviation and t-test: paired two samples for means. The result showed that (1) there were 4 patterns of public health care for elderly (elderly taking care of themselves, elderly taking care by their family, elderly taking care by agency or organization, and elderly taking care by community); and (2) there were 4 steps that important and suitable for elderly in developing suitable patterns in public health care for elderly in this area as follows: (1) studying the context of community and elderly situation, determining the roles and responsibilities of partners, and initiating a plan of taking care of elderly and improve quality of a life of elderly in community involved by the community partners with the technique of A-I-C (planning), (2) organizing activities according to a plan to take care of elderly and improve quality of a life of elderly in community involved by the community partners (action), (3) assing the elderly quality of life in community (observation), and (4) synthesizing for the lessons learned (reflection).